(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article examines the role of mineral therapy in the prevention and treatment of respiratory diseases. Mineral therapy, which encompasses the use of naturally occurring mineral waters, salts, inhalations, and halotherapy, has long been recognized as a complementary approach in pulmonary medicine. The paper discusses the mechanisms of action of mineral therapy, reviews its applications in diseases such as chronic obstructive pulmonary disease (COPD), asthma, bronchitis, and pulmonary fibrosis, and highlights its therapeutic and rehabilitative benefits.